NİKOLAY BERDYAYEV VE SARTRE FELSEFESİNDE KİŞİLİK VE ÖZGÜRLÜK PROBLEMİ - Müminov, Kasım (My University, 2016)
Bu çalışmada Berdyayev ve Sartre düşüncesinde kişilik ve özgürlük problemi ele alınmaktadır. Kişilik ve özgürlük problemi felsefe tarihi boyunca filozofların ilgisini çektiği gibi özellikle XIX. ve XX. yüzyıllarda varoluşçu felsefenin de yoğun olarak üzerinde durduğu konulardır. Biz bu çalışmada Rus düşünürü Berdyayev'in Alman düşünürlerden yola çıkarak temellendirdiği personalizm görüşlerini ve Sartre üzerindeki etkilerini incelemeye çalışacağız.Özgürlük ve kişilik sorunu, gerek Rus felsefesi gerekse Batı felsefesinde, ahlak problemini bağımsız, orijinal bir statüde felsefeye yeniden kazandırma çabası olarak kendisini gösterir. Berdyayev'e göre ahlakın kendisi bir "özgürlük felsefesi"dir. Özgürlük sadece değerler alanıyla sınırlı değil, bizzat insanın varoluş kumaşıyla ilişkilidir. Oysa Sartre'a göre özgürlüğün bir temeli yoktur. Aksine, özgürlük bütün şeylerin özüdür.

. Berdyaev's PhilosophyThis study examines the problem of personality and freedom in the thoughts of Berdyaev and Sartre. The problem of personality and freedom has attracted the attention of philosophers throughout the history and it was among the issues on which existentialist philosophy focused especially in the XIXth and XXth centuries. In this study, we will try to examine Russian philosopher Berdyaev's personalist thoughts which were grounded on the philosophy of German philosophers, and his effects on Sartre. The problem of freedom and personality shows itself, in both Russian and Western philosophy, as an effort to the sense that an independent and original status is to be given to the moral problem. This effort, in the Berdyayev and Sartre's existential philosophy, appeared as a problem of personality and freedom. But the way both thinkers solve the problem has led them to different forms of argumentation in their thoughts. In our article, it is an important point to dig deeper into the problem and to compare two different argumentations with each other. In addition, the effort of people in Berdyayev philosophy is directed to the self-recognition/self-knowledge/ self-realization. In this context, experimental side of -Existence-, for Berdyayev, is -To be internally experience of existence itself-; -It is descend to the mystery of Being-. Because, God is the realm of freedom and this area is blessed to human being. According to Berdyaev, the moral itself is -the philosophy of freedom-. Freedom is not only restricted to the values sphere; it is, at the same time, associated with the existence of human being. However, according to Sartre, freedom has no ground. On the contrary, freedom is the essence of all things.
The Problem of Personality and Freedom in the Sartre's and N. Berdyaev's Philosophy
Keywords: Din Bilimi